Maturation of filopodia shaft adhesions is upregulated by local cycles of lamellipodia advancements and retractions. - Wei Hu; Bernhard Wehrle-Haller; Viola Vogel (PLoS ONE, 2014)
While cell-substrate adhesions that form between the protruding edge of a spreading cell and flat surfaces have been studied extensively, processes that regulate the maturation of filopodia adhesions are far less characterized. Since little is known about how the kinetics of formation or disassembly of filopodia adhesions is regulated upon integration into the lamellum, a kinetic analysis of the formation and disassembly of filopodia adhesions was conducted at the leading edge of β3-integrin-EGFP-expressing rat embryonic fibroblasts spreading on fibronectin-coated glass or on soft polyacrylamide gels. Filopodia β3-integrin adhesions matured only if the lamellipodium in their immediate vicinity showed cyclic protrusions and retractions. Filopodia β3-integrin shaft adhesions elongated rapidly when they were overrun by the advancing lamellipodium. Subsequently and once the lamellipodium stopped its advancement at the distal end of the filopodia β3-integrin adhesion, these β3-integrin shaft adhesions started to grow sidewise and colocalize with the newly assembled circumferential actin stress fibers. In contrast, the suppression of the cyclic protrusions and retractions of the lamellipodium by blocking myosin light chain kinase suppressed the growth of filopodia adhesion and resulted in the premature disassembly of filopodia adhesions. The same failure to stabilize those adhesions was found for the advancing lamellipodium that rapidly overran filopodia shaft adhesions without pausing as seen often during fast cell spreading. In turn, plating cells on soft polyacrylamide gels resulted in a reduction of lamellipodia activity, which was partially restored locally by the presence of filopodia adhesions. Thus filopodia adhesions could also mature and be integrated into the lamellum for fibroblasts on soft polyacrylamide substrates.